Volume 10A: Structures and Dynamics 2020
DOI: 10.1115/gt2020-16253
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Friction-Saturated Flutter Vibrations With a Fully-Coupled Frequency Domain Method

Abstract: Flutter stability is a dominant design constraint of modern gas and steam turbines. Thus, flutter-tolerant designs are currently explored, where the resulting vibrations remain within acceptable bounds. In particular, friction damping has the potential to yield Limit Cycle Oscillations (LCOs) in the presence of a flutter instability. To predict such LCOs, it is the current practice to model the aerodynamic forces in terms of aerodynamic influence coefficients, derived for some normal modes of the linearized st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…On the other hand, in the case of strong nonlinear coupling effects (contact at the tip shroud), multi-TW states have been reported both in reduced models (Krack et al, 2017) and more realistic descriptions (Gross and Krack, 2019). Further analysis (Berthold et al, 2020) showed that nonlinear tip contact effects change the vibration modes and frequencies of the system with respect to those obtained by linearized contact conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the case of strong nonlinear coupling effects (contact at the tip shroud), multi-TW states have been reported both in reduced models (Krack et al, 2017) and more realistic descriptions (Gross and Krack, 2019). Further analysis (Berthold et al, 2020) showed that nonlinear tip contact effects change the vibration modes and frequencies of the system with respect to those obtained by linearized contact conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Decoupled approaches have allowed to find Limit Cycle Oscillations (LCO) of the structure by using the HBM procedure, while modelling aerodynamic effects from Computational Fluid Dynamics (CFD) calculations [19,20]. More recently, a fully coupled method in the frequency domain has been established [21] in order to find LCO by using harmonic formulation in both flow and structure models, and iterating in a fixed point loop between the two physics.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it was shown that the inclusion of strong nonlinear coupling effects at the tip shroud can produce multi-TW final states. The analysis was continued in [2], to show that nonlinear tip contact effects change the vibration modes and frequencies of the system with respect to those obtained with linearized contact conditions. These changes in frequencies and mode shapes have to be considered in order to correctly estimate the amplitude of the resulting limit cycle oscillations.…”
Section: Introductionmentioning
confidence: 99%